2019
DOI: 10.3390/ijms20081960
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Hypoxia Up-Regulates CCL2, RETN, and TNFα mRNAs in Adipocytes via Down-regulation of miR-452

Abstract: Sleep apnea syndrome (SAS), characterized by recurrent episodes of oxygen desaturation and reoxygenation (intermittent hypoxia [IH]), is a risk factor for insulin resistance. Recently, IH is considered to independently cause adipose tissue inflammation/dysfunction, leading to worsening insulin resistance; however, the detailed mechanism remains unknown. We exposed mouse 3T3-L1 and human SW872 adipocytes to experimental IH or normoxia for 24 h, and analyzed mRNA expression of several adipokines. We found that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 75 publications
2
59
0
Order By: Relevance
“…Yamamoto et al demonstrated that resistin production in OSA patients can be enhanced by hypoxic stress during sleep and could mediate inflammatory processes (60). An experimental study showed that the mRNA levels of resistin were significantly increased in response to intermittent hypoxia (61). In addition, CIMT is positively correlated with serum resistin levels (56).…”
Section: Discussionmentioning
confidence: 99%
“…Yamamoto et al demonstrated that resistin production in OSA patients can be enhanced by hypoxic stress during sleep and could mediate inflammatory processes (60). An experimental study showed that the mRNA levels of resistin were significantly increased in response to intermittent hypoxia (61). In addition, CIMT is positively correlated with serum resistin levels (56).…”
Section: Discussionmentioning
confidence: 99%
“…The growing interest in the interaction between IH and metabolic dysfunction is collected in a recent review [ 52 ]. In this regard, intermittent hypoxia modulates the pancreatic β cells [ 53 ], upregulates the hepatokines resulting the insulin resistance [ 54 ], exacerbates metabolic effects on diet-induced obesity [ 55 ] and the upregulation the adipokines [ 56 ]. Moreover, the intermittent hypoxia increased the systemic oxidative stress, endothelial dysfunction and rennin-angiotensin system activation augmenting the hypertension progress in animal model [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding miR-224, this miR is known for regulating adipocyte differentiation 27 , inflammation 28 , and (micro)vascular quiescence or activation 29 . Also miR-452 has a role in metabolism and inflammation because hyperglycemia regulates miR-452 expression 30 and its adipocyte-specific decrease activates a TNF-α induced inflammatory response 31 . However, more studies are needed to investigate whether these miRs pinpoint adipocyte dysfunction as a co-contributor to microvascular injury in diabetic women with LVDD or HFpEF.…”
Section: Discussionmentioning
confidence: 99%